Fracture toughness of rotationally molded polyethylene and polypropylene. Issue 1 (24th February 2017) - Saifullah, Abu; Thomas, Ben; Cripps, Robert; Tabeshfar, Kamran; Wang, Lei; Muryn, Christopher
Abstract : In this work, the fracture toughness of rotationally molded polyethylene (PE) and polypropylene (PP) was measured using J integral methods at static loading rates and at room temperature. Two different commercially available rotational molding grades PE and PP were tested in this study which have been used in various rotationally molded products such as small leisure craft, water storage tanks, and so on. Scanning electron microscope (SEM), optical microscope, differential scanning calorimetry (DSC), solid‐state nuclear magnetic resonance (solid‐state NMR), and X‐ray scattering were used to investigate the microstructure, fracture surfaces, and compare toughness properties of these materials. In PE, higher molecular weight and broader molecular weight distribution, larger amorphous and crystal region thicknesses are found to be related to higher toughness values. High molecular weight favors higher number of entanglements that improve fracture energy and broader distribution increases long chain branching of higher molecular weight fractions which creates higher entanglements at the branch sites. Larger amorphous regions promote microvoiding more easily compared to thinner amorphous regions, leading to greater plastic deformation and energy absorption. Higher crystal thickness also contributes to microvoiding in the amorphous region. For PP, greater plastic deformation observed in the fracture surfaces is related to higher fracture toughness values. POLYM. ENG. SCI., 58:63–73, 2018. © 2017 Society of Plastics Engineers